2009
DOI: 10.4103/0256-4947.55162
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index in Saudi Arabian children and adolescents: a national reference and comparison with international standards

Abstract: BACKGROUND AND OBJECTIVES:Because there are no reference standards for body mass index (BMI) in Saudi children, we established BMI reference percentiles for normal Saudi Arabian children and adolescents and compared them with international standards.SUBJECTS AND METHODS:Data from a stratified multistage probability sample were collected from the 13 health regions in Saudi Arabia, as part of a nationwide health profile survey of Saudi Arabian children and adolescents conducted to establish normal physical growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 12 publications
0
25
0
Order By: Relevance
“…suggesting the existence of double burden of both under- and overnutrition. Previous studies from KSA also confirmed the presence of double burden of malnutrition, that is, presence of both under- and overnutrition among children and adolescents [1012, 21]. Limited studies available on prevalence of child malnutrition from KSA suggest national data may alone be misleading in understanding the determinants and consequences and stoutly emphasize that it is crucial to focus on regional inequality which can be a result of ethnic as well as environmental conditions [10, 12, 19].…”
Section: Resultsmentioning
confidence: 60%
“…suggesting the existence of double burden of both under- and overnutrition. Previous studies from KSA also confirmed the presence of double burden of malnutrition, that is, presence of both under- and overnutrition among children and adolescents [1012, 21]. Limited studies available on prevalence of child malnutrition from KSA suggest national data may alone be misleading in understanding the determinants and consequences and stoutly emphasize that it is crucial to focus on regional inequality which can be a result of ethnic as well as environmental conditions [10, 12, 19].…”
Section: Resultsmentioning
confidence: 60%
“…Percentiles and z scores for age were constructed and smoothed out using the LMS methodology 2628. The BMI distribution for Saudi children and adolescents allowed for the calculation of the proportion of children and adolescents whose BMI was above the upper cut-off values 29. The prevalence of overweight and obesity were defined using the World Health Organization (WHO) cut-off values as the proportion of children whose BMI for age was above +1 and +2 standard deviation scores (SDS, z scores) respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, national growth curves for Pakistani children were significantly lower than the WHO and CDC references in the upper centiles (24). Other studies in different regions and countries have reported significant differences between their national growth curves for children and the WHO and CDC reference curves (25)(26)(27).…”
Section: Discussionmentioning
confidence: 63%